Historical genesis of the concept of number and number systems - possibilities of application in the initial teaching of mathematics (I) - Lazić, Bojan; Gordić, Snežana; Milošević, Marina (Norma, 2022)
The notion of natural number, as the basis of the entire further development of mathematics, appears as a result of gradual abstraction. The very notion of number has not been precisely defined and has changed throughout history, as has the way of recording. This paper aims to present the origin of natural numbers and their development to the present form. The essentially most important number systems that have evolved in parallel with the development of human consciousness, and which are guided by the need for man to record important events and facts, are discussed and presented. The importance of positional number systems, such as the Indo-Arabic number system we use today, was emphasized. Numerous studies show that the use of the history of mathematics in the teaching of mathematics can increase students ‘motivation and students’ interest in the subject. Based on a brief overview of existing research on the use of the history of mathematics in mathematics teaching, the paper presents examples of tasks for classroom teaching, which include elements of the history of natural numbers and number systems.